ENDODONTIC TREATMENT ON FRACTURED MANDIBULAR ANTERIOR TOOTH WITH CROWN DOWN TECHNIQUE - Raisya Aurellia Putri Lesmana; Fajar Fatriadi (FKG ULM, 2024)
Background: Trauma involving the dento-alveolar area often occurs and tends to cause tooth fractures. Fractured teeth can be at risk of infection which can lead to pain and tooth necrosis. In necrotic tooth cases, root canal treatment is one of the most common procedures to be performed to preserve the tooth. Case: A 36-year-old female patient came to RSGM Unpad with chief complaint of a broken mandibular anterior tooth. This complaint occurred 3 months ago. The patient did not complain of any pain. Previously, the tooth that the patient complained about had been restored but fell out again a month ago. History of systemic disease, family disease, and allergies was denied. Patients want their complaints to be resolved. Case Management: The treatment carried out in this case is root canal treatment. Root canal treatment consists of three main stages, namely biomechanical preparation of the root canal, root sterilization with calcium hydroxide, and obturation. The preparation technique used is crown down. The main aim of the crown down root canal preparation technique is to minimize or eliminate the amount of extruded necrotic tissue towards the apical foramen during preparation. Conclusion: Establishing a good diagnosis, as well as the use of good instrumentation in root canal treatment with a crown down preparation technique followed by single cone obturation can be an option for treating crown fracture teeth. Further follow-up is required in this case. Keywords: crown down, fracture, nonvital, root canal treatment